Solidarity insurance and financial inclusion: Attempt at measuring its impacts in the Venezuelan case - Carmona B., Pedro Luis (Cooperativismo & Desarrollo, 2018)
Purpose: The purpose of this article is to approach the measurement of solidarity insurance impacts on financial inclusion in Venezuela. Themes: The urge to generate financial inclusion with help of banking institutions and formal insurance companies becomes definite when acknowledging poverty growth in Venezuela. This is why regulators and public policy makers have developed inclusion mechanisms for the disadvantaged groups in the insurance sector, so as to mitigate risks and contribute to decrease poverty levels. However, this impact has not been quantified and the actual scope of such policy remains unknown. Development: The research based itself on the methodology proposed by the Alliance for Financial Inclusion (afi) and limited to the construction of indicators for the "Access" dimension. This was done taking into account statistical data from official institutions from 2012 to 2013. Conclusions: The impact of solidarity insurance, in terms of financial inclusion, proves to be irrelevant. The evaluation of such public policy is recommended in order to address possible failures in the design and implementation of such an important instrument for poverty reduction.